Carbon sequestration in a soil dedicated to the cultivation of pineapple (Ananas comosus (L.) under conventional management and minimum tillage - Fonseca-Vargas, Ronald (2019)
The pineapple, Ananas comosus (L.), is an important crop in Costa Rica with a planting area of approximately 38,000 ha. The objective of the study was evaluate the organic carbon content and biomass of the pineapple plant in the growing stage in a soil under conventional tillage and minimum tillage systems. The experiment was established on a farm located at 10°89›N and 84°65›W, with an altitude from 60 to 92 m above sea level and a slope of 5 % to 15 %. In conventional production, soil preparation leads to the release of carbon into the atmosphere and the loss of organic matter. Somehow, those issues have caused its cultivation to be considered one of the most degrading of the soil, nationwide. Through the application of a minimum tillage treatment and a conventional one, it was possible to appreciate that there are some variations in the nutritional levels of the plant and the soil, while in relation to the productive variables in the evaluated stage it was not possible to determine effects attributable to the difference between treatments. Neither was it possible to show differences in the soil carbon level and the C: N ratio. It is concluded that soil carbon may vary but it is necessary continue with the researcher to demonstrate that minimum pineapple tillage can bring benefits in the storage of organic carbon. It is recommended to continue with the measurements of the analyzed variables, which allow observing what is reported in other related investigations in crops.